2006
DOI: 10.1111/j.1365-2494.2006.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased concentration of water‐soluble carbohydrate in perennial ryegrass (Lolium perenne L.). Evaluation in dairy cows in early lactation

Abstract: Moorby, J. M., Evans, R. T., Scollan, N. D., MacRae, J. C., Theodorou, M. K. (2006).. Increased concentration of water-soluble carbohydrate in perennial ryegrass (Lolium perenne L.). Evaluation in dairy cows in early lactation. Grass and Forage Science, 61 (1), 52-59. Sponsorship: LINK Sustainable Livestock Production; Department for Environment, Food and Rural Affairs; Milk Development Council; Meat and Livestock Commission; Germinal Holdings LtdTwelve multiparous Holstein?Friesian dairy cows in early lactati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
120
5
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(141 citation statements)
references
References 24 publications
14
120
5
2
Order By: Relevance
“…The relatively small and non-significant dietary effect on NUE contrasted with results from cows fed a diet of around 3.2% N with elevated WSC in the diet, which showed improvement in NUE (Miller et al, 2001). In this study, the proportion of NI excreted in urine (UN/NI) was high (on average >48%; Table 3) compared with results from lactating dairy cows studies (Miller et al, 2001;Moorby et al, 2006). Our results are in contrast to the suggestion from the review of Edwards et al (2007) that increased NUE and decreased UN/NI of dairy cows should be observed when WSC : N increased from 4.4 to 8.1 g/g.…”
Section: N Metabolismcontrasting
confidence: 66%
“…The relatively small and non-significant dietary effect on NUE contrasted with results from cows fed a diet of around 3.2% N with elevated WSC in the diet, which showed improvement in NUE (Miller et al, 2001). In this study, the proportion of NI excreted in urine (UN/NI) was high (on average >48%; Table 3) compared with results from lactating dairy cows studies (Miller et al, 2001;Moorby et al, 2006). Our results are in contrast to the suggestion from the review of Edwards et al (2007) that increased NUE and decreased UN/NI of dairy cows should be observed when WSC : N increased from 4.4 to 8.1 g/g.…”
Section: N Metabolismcontrasting
confidence: 66%
“…In Wales, the potential of using perennial ryegrass with enhanced levels of water-soluble carbohydrates (WSC) was investigated in dairy cows using experimental perennial ryegrass varieties bred to contain a high concentration of WSC (Miller et al, 2001;Moorby et al, 2006). The concept is that provision of readily available energy can have a significantly positive influence on N utilisation efficiency and animal performance.…”
Section: Variation Of Nutrient Supply At Grazing Relative To Animal Rmentioning
confidence: 99%
“…They observed a higher digestible DMI (+ 1.5 kg d ) and NUE (+ 7%), and a lower proportion of urinary N (10%) in cows fed the HS cultivar. Two years later in a similar study with early lactation cows, Moorby et al (2006) ) and total DMI (18.8 vs. 16.6) and a non significant tendency to a higher milk yield (+ 2.3 kg d -1…”
Section: Supplementation Criteria Authorsmentioning
confidence: 99%